The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s13139-017-0508-3
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Botulinum Toxin for Preventing Salivary Gland Toxicity after PSMA Radioligand Therapy: an Empirical Proof of a Promising Concept

Abstract: The dose-limiting salivary gland toxicity of Ac-labelled PSMA for treatment of metastatic, castration-resistant prostate cancer remains unresolved. Suppressing the metabolism of the gland by intraparenchymal injections of botulinum toxin appears to be a promising method to reduce off-target uptake. AGa-PSMA PET/CT scan performed 45 days after injection of 80 units of botulinum toxin A into the right parotid gland in a 63-year-old patient showed a decrease in the SUVmean in the right parotid gland of up to 64% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 5 publications
(5 reference statements)
1
52
0
2
Order By: Relevance
“…Some studies have shown that the uptake of PSMA-targeted radioligands in salivary gland tissues may be caused by both nonspecific and PSMAspecific uptake. However, the exact proportion of each form of uptake is still uncertain, and the mechanism of the nonspecific uptake is still unclear [29][30][31][32]. Recently, it has been reported that the accumulation of PSMA-targeted radioligands in salivary gland tissue is mainly caused by nonspecific uptake [18,33].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the uptake of PSMA-targeted radioligands in salivary gland tissues may be caused by both nonspecific and PSMAspecific uptake. However, the exact proportion of each form of uptake is still uncertain, and the mechanism of the nonspecific uptake is still unclear [29][30][31][32]. Recently, it has been reported that the accumulation of PSMA-targeted radioligands in salivary gland tissue is mainly caused by nonspecific uptake [18,33].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Teymoortash et al investigated the effect of botulinum toxin injections to the SGs with head and neck cancer undergoing external-beam radiotherapy (12). Earlier this year, our group translated that approach into tracer uptake blockade and achieved a 64% decrease in 68 Ga-PSMA uptake in an injected parotid gland, leading to the first proof-of-concept publication on the topic (13) and heralding a hypothesis of nonspecific tracer accumulation. Given the possibility of some specific binding of PSMA radioligands in the SGs, local application of cold compounds or inhibitors of PSMA such as 2-(phosphonomethyl) pentanedioic acid (14) are also being investigated.…”
mentioning
confidence: 99%
“…Wide-ranging but ultimately unsuccessful attempts have also been made to nonspecifically mitigate kidney and salivary gland toxicities. These strategies have included coadministration of gelofusine (19) and mannitol (41) to inhibit renal reabsorption, facial application of ice packs to reduce salivary gland blood flow (42), and salivary gland injection of botulinum toxin (43), all of which offered little or no benefit with the exception of the latter. However, this invasive approach has no effect on kidneys and its benefit needs to be confirmed in larger, more controlled studies.…”
Section: Discussionmentioning
confidence: 99%